Integrasi Ilmu Kisah Nabi Musa dan Nabi Khidir dalam Q.S. Al-Kahfī [18]: 60-82 - Romadhoni, Moh. Wildan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2022)
This study focuses on analyzing the story of the prophet Musa and the prophet Khidir in Q.S. al-Kahfī [18]: 60-82. The aim is to uncover and discover the branches of disciplines that are integrated in it, both general science and religious science. This is important in order to understand a story in the Qur'an holistically and comprehensively. The approach used in this study is a qualitative approach using library research and data analysis using content analysis methods. The results of this study indicate that the story of the prophet Musa and the prophet Khidir contains several integrated scientific disciplines. For example, when the prophet Khidir made the decision to leak the boat, he had considered the risks he faced. First, if the boat is not leaked it will be confiscated and will never be returned so that the boat owner loses his job. Second, if the boat is leaked then the boat is damaged. Both of these decisions have risks, but the prophet Khidir took a less risky decision, which was to leak the boat. In this story there are disciplines that are integrated in it, namely Management science which is illustrated by two points, namely; decision making and risk management. In addition, the author also identifies the existence of various other disciplines such as; Sufism, psychology, education and logic.